Pengembangan Kecerdasan Spiritual pada Peserta Didik melalui Aktivitas Keagamaan - Siti Qoni'ah (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2019)
The effort of the formation or establishment of spiritual intelligence on the students is done by planting Islamic religious values in PAI learning and character planting which then implemented in the form of daily behavior that reflects the character or identity of each individual learners and is supported by the religious program that have been compiled by the school institution. This study aims to (1) Describe and analyze the process of the formation of spiritual intelligence on students or learners (2) Describe and analyze the implementation of religious activity programs in shaping spiritual intelligence in learners (3) Describe and analyze the impact of the formation of spiritual intelligence in learners through the implementation of the religious program. This research uses qualitative research approach. The type of research used in this research is case study and case studies and multiple cases design. Data collection uses observation, interview and documentation. The results showed that in SD Plus Nurul Hikmah the formation of spiritual intelligence is done by planting the values of faith and pillars of Islam as well as the implanting of characters in learning PAI and applied through the program of religious activity and application of character, while in MIN Konang the formation of spiritual intelligence done by planting The prophet characteristics and the prophet`s story in learning PAI as well as the planting of characters applied in the form of religious activity and the application of character. The formation of spiritual intelligence in both schools can be concluded that overall spiritual intelligence in learners has been formed, it is known from attitudes, behaviors and religious activities always performed by learners at both school and at home, although the results have not reached one hundred percent, But both school is always working in terms of improving the strategy of the formation of spiritual intelligence in learners.